Oleaginous yeast for biofuel and oleochemical production. (June 2019) - Spagnuolo, Michael; Yaguchi, Allison; Blenner, Mark
Highlights: The yeasts, Cutaneotrichosporon oleaginosus, Lipomyces starkeyi, and Rhodosporidium toruloides, grow on a wide range of substrates and naturally outperform Yarrowia lipolytica . Currently, Y. lipolytica has the most tools and widest range of engineered products. Accelerating development of genetic engineering tools for C. oleaginosus, R. toruloides, and L. starkeyi will make these hosts favorable for bioenergy production. Abstract : Current transportation fuels derived from petroleum can also be made from microbial systems. In particular, oleaginous yeast have naturally evolved high flux pathways for fatty acids in the form of neutral lipids, which can be converted into a variety of drop-in fuels. Here, we describe the recent advances in the use of the four most popular oleaginous yeasts for making lipids and other potential fuels – Yarrowia lipolytica, Lipomyces starkeyi, Rhodosporidium toruloides, and Cutaneotrichosporon oleaginosus . The paper is divided into three major sections focusing on (1) the important natural complex phenotypes of each yeast; (2) the development of metabolic engineering tools for each yeast; and (3) demonstrations of metabolic engineering in each yeast. At the end of each section, we provide our assessment, of which yeast is most promising in the near and long term for bioenergy production.